PEMISAHAN LARUTAN MENJADI FRAKSI-FRAKSINYA MENGGUNAKAN KHROMATOGRAFI ANNULAR KONTINYU - S Retnowati, Diah (Diponegoro University, 2009)
Chromatography can be used for analysis or separation. This review describes continuous annularchromatography for separation of enantiomers or isomers. These type molecules are hardly separatedwith conventional separation, and therefore need a good separation method. Continuous AnnularChromatography consists of a rotating annular bed. The annulus is formed between two concentriccylinders, and the resin is packed in the annulus. At fix position at the top of the bed, four solutions arecontinuously fed, the feed mixture to be separated, a displacer solution, a regenerant and a rinse. TheAnnulus is slowly rotated with the result that different zones will formed helices of characteristic anglewhich can be collected at variations fixed points around the bottom of the bed.